2019
DOI: 10.1029/2018gb005992
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning (kNN) Approach to Predicting Global Seafloor Total Organic Carbon

Abstract: Seafloor properties, including total organic carbon (TOC), are sparsely measured on a global scale, and interpolation (prediction) techniques are often used as a proxy for observation. Previous geospatial interpolations of seafloor TOC exhibit gaps where little to no observed data exists. In contrast, recent machine learning techniques, relying on geophysical and geochemical properties (e.g., seafloor biomass, porosity, and distance from coast), show promise in making comprehensive, statistically optimal predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(156 citation statements)
references
References 21 publications
(36 reference statements)
2
99
0
Order By: Relevance
“…Previous studies have predicted OC concentrations and sediment porosity separately to calculate OC stocks (Diesing et al, 2017;Lee et al, 2019;Wilson et al, 2018). Here, we first calculate OC density from concurrent measurements of OC concentrations and sediment dry bulk densities or porosities.…”
Section: Organic Carbon Densitymentioning
confidence: 99%
“…Previous studies have predicted OC concentrations and sediment porosity separately to calculate OC stocks (Diesing et al, 2017;Lee et al, 2019;Wilson et al, 2018). Here, we first calculate OC density from concurrent measurements of OC concentrations and sediment dry bulk densities or porosities.…”
Section: Organic Carbon Densitymentioning
confidence: 99%
“…A 10-fold cross validation (CV), an approach frequently used in model validation (e.g. Li et al, 2011;Gasch et al, 2015;Ließ et al, 2016;Meyer et al, 2016bMeyer et al, , 2018, was applied to validate the RF model. CV involved partitioning the dataset into 10 equally sized folds.…”
Section: Model Validationmentioning
confidence: 99%
“…Studies comparing RF against other machine learning algorithms reported different trends: in some cases, RF was superior in terms of prediction performance (e.g. Li et al, 2011;Cracknell and Reading, 2014), whereas in other cases, no strong differences were observed between the different methods (e.g. Goetz et al, 2015;Meyer et al, 2016b).…”
Section: Suggestions For Further Improvement Of Performancementioning
confidence: 99%
See 2 more Smart Citations